2019
DOI: 10.1111/jth.14603
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid modulates the cellular immune profile after traumatic brain injury in mice without hyperfibrinolysis

Abstract: Background Traumatic brain injury (TBI) is known to promote immunosuppression, making patients more susceptible to infection, yet potentially exerting protective effects by inhibiting central nervous system (CNS) reactivity. Plasmin, the effector protease of the fibrinolytic system, is now recognized for its involvement in modulating immune function. Objective To evaluate the effects of plasmin and tranexamic acid (TXA) on the immune response in wild‐type and plasminogen‐deficient (plg−/−) mice subjected to TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Animal studies of trauma have found results similar to that of Syrovets et al, where Sprague-Dawley rats exposed to hemorrhagic shock for 60 minutes (MAP of 30 mm Hg) had a blunted IL-1 and IL-10 response if treated with TXA and also a reduction in pulmonary edema and mesenteric lymph node hyperplasia, although this study had mixed effects, with some proinflammatory sequela in the TXA group observed to include worse cardiac injury. 27 The ability of TXA to reduce proinflammatory IL1-β levels has also been demonstrated in human clinical studies of cardiac surgery patients, 28 where interestingly TXA also led to reduced postoperative infections (particularly in nondiabetic patients) and generated a more favorable, less immunosuppressed cellular immune profile that has been extensively studied by Draxler et al 29 In another study using a well-known mouse cremaster model of I/R injury, Reichel et al demonstrated that plasmin inhibitors including TXA led to significant reductions in leukocyte adhesion and migration across the microvascular endothelium during the reperfusion phase. 30 They found that this effect was dependent on mast cell activation, where plasmin led to increased RNA expression of 5-lipoxygenase and lyso-PAF-acetyltransferase that facilitated leukotriene and platelet-activating factor production, which are well known to recruit, prime, and activate neutrophils.…”
mentioning
confidence: 95%
“…Animal studies of trauma have found results similar to that of Syrovets et al, where Sprague-Dawley rats exposed to hemorrhagic shock for 60 minutes (MAP of 30 mm Hg) had a blunted IL-1 and IL-10 response if treated with TXA and also a reduction in pulmonary edema and mesenteric lymph node hyperplasia, although this study had mixed effects, with some proinflammatory sequela in the TXA group observed to include worse cardiac injury. 27 The ability of TXA to reduce proinflammatory IL1-β levels has also been demonstrated in human clinical studies of cardiac surgery patients, 28 where interestingly TXA also led to reduced postoperative infections (particularly in nondiabetic patients) and generated a more favorable, less immunosuppressed cellular immune profile that has been extensively studied by Draxler et al 29 In another study using a well-known mouse cremaster model of I/R injury, Reichel et al demonstrated that plasmin inhibitors including TXA led to significant reductions in leukocyte adhesion and migration across the microvascular endothelium during the reperfusion phase. 30 They found that this effect was dependent on mast cell activation, where plasmin led to increased RNA expression of 5-lipoxygenase and lyso-PAF-acetyltransferase that facilitated leukotriene and platelet-activating factor production, which are well known to recruit, prime, and activate neutrophils.…”
mentioning
confidence: 95%
“…19 In a TBI animal model, a potentially beneficial inflammatory and immune modulation were demonstrated after TXA administration. 20 Furthermore, TXA was also shown to be associated with elevated immune activation in a post-TBI pneumonia animal model. 21 Aside from the included studies, there was an observational study reported that TXA administration in patients with cerebral contusions or traumatic subarachnoid hemorrhage was independently associated with a reduced mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…TXA has been shown to modulate pulmonary inflammation in trauma-induced acute lung injury [19]. In a TBI animal model, a potentially beneficial inflammatory and immune modulation were demonstrated after TXA administration [20]. Furthermore, TXA was also shown to be associated with elevated immune activation in a post-TBI pneumonia animal model [21].…”
Section: Discussionmentioning
confidence: 99%